Influence of cement replacement with limestone filler on the properties of concrete - Tešić Ksenija (Society for Materials and Structures testing of Serbia, 2021)
This paper presents an experimental research of one type of green concrete in which Portland cement was replaced with two types of limestone filler of the same origin and mineralogical composition, but with a different fineness of particles. Ten concrete mixtures were designed in which 0%, 15%, 30% and 45% (by mass) of cement were replaced with filler. The water to cement ratio for each mixture was constant (w/c=0.54), and the water to powder ratio was decreasing with increasing cement replacement. Particle size distribution was selected using Funk and Dinger, as well as using Fuller's model. The results showed that it is possible to increase the compressive strength of concrete by reducing 45% of cement, but further research should be focused on improving the workability.